VARIASI BAHASA PADA TAYANGAN KICK ANDY DALAM EPISODE “NGELMU SAMPAI MATI” - Fitri Puji Rahmawati; Sumarlam Sumarlam (Universitas Muhammadiyah Surakarta, 2016)
This study aims to describe the literary form of language variationcontained in the show Kick Andy episode, “Learn to Death”. The method used isdescriptive qualitative. Provision of data is done by methods refer to listen andunderstand the data linguistic oral form of data in the data source view KickAndy.The technique is a recording and log techniques. The analysis of data usinga unified method. The research result describe that form of language variation inthis show consists of variations in terms of formality, speakers, use, and means.1) The variation in terms of formality using a variety offamiliar, 2) variationsBetawiand Batak dialect speakers are used, 3) variations in the use of more useof registers in the field of education, 4) Variation means used in this show is avariation of oral.